2016
DOI: 10.1007/s10815-016-0682-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of epigenetics in idiopathic male infertility

Abstract: Infertility is a complex disorder with multiple genetic and environmental causes. Although some specific mutations have been identified, other factors responsible for sperm defects remain largely unknown. Despite considerable efforts to identify the pathophysiology of the disease, we cannot explain the underlying mechanisms of approximately half of infertility cases. This study reviews current data on epigenetic regulation and idiopathic male infertility. Recent data have shown an association between epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 136 publications
0
70
1
5
Order By: Relevance
“…In conclusion, DNA methylation has been closely associated with male infertility (66,121). Understanding the mechanisms underlying DNA methylation is particularly important in order to develop therapeutic strategies for male genital system diseases caused by abnormal sperm DNA methylation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In conclusion, DNA methylation has been closely associated with male infertility (66,121). Understanding the mechanisms underlying DNA methylation is particularly important in order to develop therapeutic strategies for male genital system diseases caused by abnormal sperm DNA methylation.…”
Section: Resultsmentioning
confidence: 98%
“…Using restriction landmark genomic scanning technology, DNA methylation was detected for chromosomes 6, 20 and 22 in spermatozoa, with numerous sites in sperm and somatic cells exhibiting varying degrees of methylation (66)(67)(68). The extent of methylation in sperm cells was significantly increased, as compared with fibroblasts (>20%), liver cells (10%), and CD4 + and CD8 + lymphocytes (5%) (68,69 (65,69,70).…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 99%
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the abnormalities in the DNA methylation patterns and histone modification of spermatozoa contribute in the decline of male fecundity which has been identified in 15%-30% of infertile problems in male Jenkins, Aston, Meyer et al, 2016;Soubry, 2015). Interestingly, several of previous studies have revealed a correlation between epigenetic alterations and infertility problems in male (Gunes, Arslan, Hekim, & Asci, 2016;Tian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%